A parametric study of tsunami fission generation in a bay geometry based on numerical simulation. Issue 1 (2nd January 2018) - Yamanaka, Yusuke; Sato, Shinji; Shimozono, Takenori; Tajima, Yoshimitsu
ABSTRACT: Tsunami fission generates short waves at the front face of tsunami and these short waves may expand the inundation area, increase the hydrodynamic forces exerted on structures, and amplify the damage to coastal communities. It is therefore important to understand to what extent the tsunami fission generates such short wave components under variable conditions for development of better tsunami disaster mitigation strategies and plannings. This study carried out numerical experiments to describe under which conditions the tsunami fission occurs in a bay. The experiments indicated that the amplification of the nearshore tsunami height induced by the narrowing bay geometry and the bay-scale resonance enhance the tsunami fission. Based on the computations, a parametric diagram for the occurrence of tsunami fission was proposed in terms of the tsunami properties, the effect of bay geometry and the bay resonance. The developed diagram was applied to Sendai, Ryori, Yoshihama, and Toni Bays, which were affected by the 2011 Tohoku Tsunami. The proposed diagram consistently explained the occurrence of tsunami fission in Sendai Bay and in Ryori Bay as observed in the video footage. The diagram also suggested that the tsunami fission would have occurred in Yoshihama Bay. A high-resolution numerical computation was performed to simulate the tsunami deformation in the Yoshihama Bay and Toni Bay based on a nonlinear dispersive wave model. The result supported the validity of the diagram in describing the generation of tsunami fission in Yoshihama Bay.